Two-State Quantum Systems Revisited: A Clifford Algebra Approach - Amao, Pedro; Castillo, Hernan (Advances in applied Clifford algebras, 2021)
We revisit the topic of two-state quantum systems using the Clifford Algebra in three dimensions C l 3 . In this description, both the quantum states and Hermitian operators are written as elements of C l 3 . By writing the quantum states as elements of the minimal left ideals of this algebra, we compute the energy eigenvalues and eigenvectors for the Hamiltonian of an arbitrary two-state system. The geometric interpretation of the Hermitian operators enables us to introduce an algebraic method to diagonalize these operators in C l 3 . We then use this approach to revisit the problem of a spin-1/2 particle interacting with an external arbitrary constant magnetic field, obtaining the same results as in the conventional theory. However, Clifford algebra reveals the underlying geometry of these systems, which reduces to the Larmor precession in an arbitrary plane of C l 3 .